Type of Collaboration In Management Overstock Rice 2 Million Tons of Sustainable South Sulawesi Provincial Government Between the Military Regional Command VII / Wirabuana - Bachtiar; Sangkala; Haselman; Yunus, Muhammad (IJRDO - Journal of Social Science and Humanities Research, 2016)
Research on the collaboration between the two institutions, namely government South Sulawesi Provincial Government with Command Daerah Military (Military Command) VII / Wirabuana in order to increase overstock rice 2 million tonnes me n a rik to be studied mainly related to the type of collaboration management that is applied to both parties. In order to achieve the objectives of the study, the research approach used was qualitative. The research results indicate that the type of collaboration that is used in the management of collaborative management between the Government of South Sulawesi province with the Regional Military Command (Kodam) VII/Wirabuana to reach 2 million tonnes of rice overstock sustainable is "temporary task force".